THU0567 Using the National Database of Rheumatic Diseases by Ir-Net in Japan to Investigate Factors Influencing Medium-Term Physical Function following Total Knee and Total Hip Arthroplasty. (10th June 2014) - Ohashi, S.; Kadono, Y.; Yasui, T.; Ono, K.; Oka, H.; Nishino, J.; Tanaka, S.; Mori, T.; Masuda, K.; Iwasawa, M.; Matsui, T.; Tohma, S.
Abstract : Objectives: The present study used the National Database of Rheumatic Diseases by iR-net in Japan (NinJa) to investigate factors that influence physical function in rheumatoid arthritis (RA) patients following total knee arthroplasty (TKA) or total hip arthroplasty (THA). Methods: Analysis was conducted on 122 TKA patients (13 men, 109 women, 62.3[10.4] years) and 59 THA patients (6 men, 53 women, 61.8[8.9] years) registered with NinJa between 2003 and 2012 who had 5 years of follow-up without any other surgical procedures. Patients were classified into two groups based on whether modified Health Assessment Questionnaire (mHAQ) scores had decreased (improvement group) or increased (deterioration group) during the 5-year postoperative period as an indicator of medium-term physical function. Inter-group comparison was conducted regarding preoperative disease duration, stage, class, C-reactive protein (CRP) level, erythrocyte sedimentation rate, scores for mHAQ, patient's pain visual analog scale (PtPainVAS), patient's generalized visual analogue scale (PtGVAS), doctor's visual analog scale (DrVAS), disease activity score 28 (DAS28), DAS28-CRP, clinical disease activity index (CDAI), simplified disease activity index (SDAI) and age at the time of surgery. Pre- and postoperative changes in DAS28, DAS28-CRP, CDAI and SDAI were compared as indicators of disease activity. Results: Among TKA patients, the improvement group (n=40) was significantly younger at the time of surgery (58.6[9.9] years vs. 66.2[9.6] years) and showed higher preoperative mHAQ, PtPainVAS, PtGVAS, DrVAS, DAS28, DAS28 CRP, CDAI and SDAI compared with the deterioration group (n=37) (p<0.05). Among THA patients, the improvement group (n=22) showed significantly higher preoperative PtPainVAS, PtGVAS, and DrVAS scores against the deterioration group (n=18). Meanwhile, for both TKA and THA patients, significantly greater improvements in all disease activity indicator scores at 5 years postoperatively were observed for the improvement group versus the deterioration group (TKA: DAS28, 74.5% vs. 102.6%; DAS28-CRP, 72.3% vs. 98.5%; CDAI, 56.0% vs. 133.3%; and SDAI, 52.9% vs. 118.8%. THA: DAS28, 69.4% vs. 79.4%; DAS28-CRP, 63.9% vs. 79.9%; CDAI, 54.9% vs. 70.4%; and SDAI, 50.0% vs. 62.2%, where preoperative scores =100%) (Fig. 1). Conclusions: The present findings indicate that the remedial effects of TKA and THA on physical function in RA patients are maintained postoperatively by sufficient control of disease activity even in patients with preoperatively poor physical function and high disease activity. Disclosure of Interest: : None declared DOI: 10.1136/annrheumdis-2014-eular.3985